Profitability Ratio Analysis in Measuring Financial Performance in Islamic Banking Listed on the IDX (2021-2023) - Faizah, Iva; Ariyadi, Ariyadi; Ella May Rina, Dian; Yalil Rezkiani, Elis (Al-Mashrof: Islamic Banking and Finance, 2024)
This research discusses profitability ratio analysis in measuring the financial performance of sharia banking listed on the IDX for the 2021-2023 period. Profitability ratios are the ability of a company to generate profits during a certain period. This ratio also provides a measure of the level of effectiveness of a company's management. The research method used is quantitative descriptive. The results of analysis of profitability ratios such as Net Profit Margin (NPM) and Gross Profit Margin (GPM) from several Islamic banks show significant fluctuations and changes from year to year. Bank Aladin, BTPN and Panin Dubai showed significant variations in their ROA and ROE over the period. Aladin Bank in particular experienced difficulty in generating positive gross profits. This research aims to provide a deeper understanding of the financial performance of Islamic banks and provide recommendations for improving asset and equity management in order to improve the financial performance of these banks in the future.